Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

Trả lời:
\(P=\left(\frac{x-\sqrt{x}+2}{x-\sqrt{x}-2}-\frac{x}{x-2\sqrt{x}}\right)\div\frac{1-\sqrt{x}}{2-\sqrt{x}}\left(ĐK:x>0,x\ne1,x\ne4\right)\)
\(P=\left[\frac{x-\sqrt{x}+2}{\left(\sqrt{x}-2\right).\left(\sqrt{x}+1\right)}-\frac{x}{\sqrt{x}.\left(\sqrt{x}-2\right)}\right]\div\frac{-\left(\sqrt{x}-1\right)}{-\left(\sqrt{x}-2\right)}\)
\(P=\left[\frac{x-\sqrt{x}+2}{\left(\sqrt{x}-2\right).\left(\sqrt{x}+1\right)}-\frac{\sqrt{x}}{\sqrt{x}-2}\right]\div\frac{\sqrt{x}-1}{\sqrt{x}-2}\)
\(P=\left[\frac{x-\sqrt{x}+2}{\left(\sqrt{x}-2\right).\left(\sqrt{x}+1\right)}-\frac{\sqrt{x}.\left(\sqrt{x}+1\right)}{\left(\sqrt{x}-2\right).\left(\sqrt{x}+1\right)}\right]\times\frac{\sqrt{x}-2}{\sqrt{x}-1}\)
\(P=\left[\frac{x-\sqrt{x}+2-x-\sqrt{x}}{\left(\sqrt{x}-2\right).\left(\sqrt{x}+1\right)}\right]\times\frac{\sqrt{x}-2}{\sqrt{x}-1}\)
\(P=\left[\frac{-2\sqrt{x}+2}{\left(\sqrt{x}-2\right).\left(\sqrt{x}+1\right)}\right]\times\frac{\sqrt{x}-2}{\sqrt{x}-1}\)
\(P=\frac{-2.\left(\sqrt{x}-1\right)}{\left(\sqrt{x}-2\right).\left(\sqrt{x}+1\right)}\times\frac{\sqrt{x}-2}{\sqrt{x}-1}\)
\(P=\frac{-2}{\sqrt{x}+1}\)
Vậy \(P=\frac{-2}{\sqrt{x}+1}\)với \(x>0,x\ne1,x\ne4\)

a) \(\frac{1}{\sqrt{x}-1}+\frac{1}{1+\sqrt{x}}=\frac{1+\sqrt{x}}{\left(\sqrt{x}-1\right)\left(1+\sqrt{x}\right)}+\frac{\sqrt{x}-1}{\left(\sqrt{x}-1\right)\left(1+\sqrt{x}\right)}=\frac{2\sqrt{x}}{x-1}\)( x > 0 ; x ≠ 1 )
b) \(\frac{1}{\sqrt{x}+2}-\frac{2}{\sqrt{x}-2}-\frac{\sqrt{x}}{4-x}=\frac{1}{\sqrt{x}+2}-\frac{2}{\sqrt{x}-2}+\frac{\sqrt{x}}{x-4}\)
\(=\frac{\sqrt{x}-2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}-\frac{2\left(\sqrt{x}+2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}+\frac{\sqrt{x}}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}\)
\(=\frac{\sqrt{x}-2-2\sqrt{x}-4+\sqrt{x}}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}=\frac{-6}{x-4}\)( x > 0 ; x ≠ 4 )
a) Với \(x>0\)và \(x\ne1\)ta có:
\(\frac{1}{\sqrt{x}-1}+\frac{1}{1+\sqrt{x}}+1\)
\(=\frac{\sqrt{x}+1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}+\frac{\sqrt{x}-1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}+\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\)
\(=\frac{\sqrt{x}+1+\sqrt{x}-1+x-1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}=\frac{x+2\sqrt{x}+1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\)
\(=\frac{\left(\sqrt{x}+1\right)^2}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}=\frac{\sqrt{x}+1}{\sqrt{x}-1}\)
b) Với \(x>0\)và \(x\ne4\)ta có:
\(\frac{1}{\sqrt{x}+2}-\frac{2}{\sqrt{x}-2}-\frac{\sqrt{x}}{4-x}=\frac{1}{\sqrt{x}+2}-\frac{2}{\sqrt{x}-2}-\frac{\sqrt{x}}{x-4}\)
\(=\frac{\sqrt{x}-2}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}-\frac{2\left(\sqrt{x}+2\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}+\frac{\sqrt{x}}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}\)
\(=\frac{\left(\sqrt{x}-2\right)-2\left(\sqrt{x}+2\right)+\sqrt{x}}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}\)
\(=\frac{\sqrt{x}-2-2\sqrt{x}-4+\sqrt{x}}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}=\frac{-6}{x-4}\)

\(=\frac{\sqrt{x}}{\sqrt{x}-2}+\frac{\sqrt{x}-1}{\sqrt{x}+2}+\frac{\sqrt{x}-10}{\left(\sqrt{x}+2\right)\left(\sqrt{x}-2\right)}\)
\(=\frac{\sqrt{x}\left(\sqrt{x}+2\right)+\left(\sqrt{x}-1\right)\left(\sqrt{x}-2\right)+\left(\sqrt{x}-10\right)}{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}\)
\(=\frac{x+2\sqrt{x}+x-2\sqrt{x}-\sqrt{x}+2+\sqrt{x}-10}{\left(\sqrt{x}+2\right)\left(\sqrt{x}-2\right)}\)
\(=\frac{2x-8}{x-4}\)
\(=\frac{2\left(x-4\right)}{x-4}\)
\(=2\)

1, với x > 0 ; x khác 1 ; 4
a, \(P=\left(\dfrac{x+\sqrt{x}-x-2}{\sqrt{x}+1}\right):\left(\dfrac{\sqrt{x}\left(\sqrt{x}-1\right)+\sqrt{x}-4}{x-1}\right)\)
\(=\dfrac{\sqrt{x}-2}{\sqrt{x}+1}:\dfrac{x-4}{x-1}=\dfrac{\sqrt{x}-1}{\sqrt{x}+2}\)
b, Ta có P > 0 => \(\sqrt{x}-1>0\Leftrightarrow x>1\)
Kết hợp đk vậy x > 1 ; x khác 4

1. \(VT=\sqrt{7+4\sqrt{3}}-\sqrt{7-4\sqrt{3}}\)
\(=\sqrt{2^2+2.2.\sqrt{3}+\left(\sqrt{3}\right)^2}-\sqrt{2^2-2.2.\sqrt{3}+\left(\sqrt{3}\right)^2}\)
\(=\sqrt{\left(2+\sqrt{3}\right)^2}-\sqrt{\left(2-\sqrt{3}\right)^2}\)
\(=2+\sqrt{3}-2+\sqrt{3}=VP\)
Bài 1.
Ta có : \(\sqrt{7+4\sqrt{3}}-\sqrt{7-4\sqrt{3}}\)
\(=\sqrt{3+4\sqrt{3}+4}-\sqrt{3-4\sqrt{3}+4}\)
\(=\sqrt{\left(\sqrt{3}+2\right)^2}-\sqrt{\left(\sqrt{3}-2\right)^2}\)
\(=\left|\sqrt{3}+2\right|-\left|\sqrt{3}-2\right|\)
\(=\sqrt{3}+2-\left(2-\sqrt{3}\right)\)
\(=\sqrt{3}+2-2+\sqrt{3}=2\sqrt{3}\left(đpcm\right)\)